The Methodology for Forecasting of Prices for Innovative Products with Reference to Quality Change in Time - GREKOV Igor Evgenevich; RIABININA Natalie Ivanovna; SEMENOVA Elena Mikhailovna; TEREKHOVA Lidia Anatolievna; TRUBINA Irina Olegovna (Communications of International Proceedings, 2021)
The article is devoted to the study of the issues of forecasting the prices of goods in the framework of an innovative project. The purpose of the study is to identify methods for adjusting prices, taking into account changes in the quality of innovative products over time. The authors presented a methodology for calculating hedonic regressions to determine the structure of the value of a product depending on certain characteristics. It was revealed that the choice of the price adjustment method taking into account the quality of products depends on the degree of "novelty" of the analyzed new product. The analysis of the choice model of the price adjustment method for evolutionary and revolutionary goods of innovative production is carried out. It is proposed to use hedonic indices to predict the prices of duplicate goods and modifications of goods, which will serve as indicators of price changes quality-adjusted. For revolutionary products, the authors propose to use the method of conditional calculation which makes it possible to predict the price dynamics in the future for a completely new product.
Keywords: Innovations; Price Forecasting; Forecasting Methods; Evolutionary And Revolutionary Goods